ASHARI’S SCHOOL OF KALAM - Годованець, Н. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Carried theological analysis Ashari’s school of Kalam, which suggests that at all stages of development of Kalam in general it was characterized by: rationalism, approval absolute priority of reason over faith, anti-authoritarianism, denial of blind adherence to religious authority, a critical spirit, the denial of any creeds, the adoption of which is not accompanied by doubts about their truth; education among the masses the ability of critical thinking; pantheistic focus on issues of the relationship between God and the world. Asharites proclaimed the absolute priority of reason over faith, and doubt – a methodological principle of cognition.